Design and implementation of customized workflow configuration platform for electric power company. (November 2021) - Huang, Wenjing; Zhu, Junyu; Gao, Yi; Liu, Ge; Yuan, Yi; Li, Junjie; Yu, Pei; Long, Quan
Abstract: As power supply company carries out work to optimize the business environment, much problems such as asymmetric information about electricity consumption of electricity users, poor professional interaction channels and low work efficiency have emerged while the level of power supply services has been improved. Relying on the Internet of Things (IoT) platform of power supply company, open graphic library (OpenGL) technology, Activiti engine and Java programming technology and other mature technologies, a set of graphical workflow configuration platform has been built to support the customization of the electricity users. The platform graphically implements the construction of power business workflow, using drag-and-drop components and model-driven logic to create front-end web and mobile applications. The workflow platform conducts compliance audit during workflow configuration, keeps business information strictly outside the negative list, and each work is automatically initiated, executed and associated to abstract behaviours with high application rate and comprehensiveness based on rich and diverse work scenarios to meet the needs of Beibei power supply company. After the workflow configuration platform was applied, the business management and execution efficiency of the power supply company was improved by more than 30%.